Ontology-Based Device Descriptions and Device Repository for Building Automation Devices. (4th October 2010) - Dibowski, Henrik; Kabitzsch, Klaus
Abstract : Device descriptions play an important role in the design and commissioning of modern building automation systems and help reducing the design time and costs. However, all established device descriptions are specialized for certain purposes and suffer from several weaknesses. This hinders a further design automation, which is strongly needed for the more and more complex building automation systems. To overcome these problems, this paper presents novel Ontology-based Device Descriptions (ODDs) along with a layered ontology architecture, a specific ontology view approach with virtual properties, a generic access interface, a triple store-based database backend, and a generic search mask GUI with underlying query generation algorithm. It enables a formal, unified, and extensible specification of building automation devices, ensures their comparability, and facilitates a computer-enabled retrieval, selection, and interoperability evaluation, which is essential for an automated design. The scalability of the approach to several ten thousand devices is demonstrated.